Impact of buffer size and TTL on DTN routing protocols in intermittently connected mobile networks - Sharif Hossen, Md.; Masum Billah, Md.; Yasmin, Suraiya (International Journal of Engineering and Technology, 2018)
Delay-Tolerant Networks (DTNs) are kinds of networks where there does not exist any complete end-to-end route from source to destination. Such networks can also be referred to as Intermittently Connected Mobile Networks (ICMNs), which are featured by asymmetric data rates, large delay, limited resources and high error rates. In this network, size of buffer and Time-to-Live (TTL) for fixed number of nodes and message generation rates contribute to the network performance because of limited resources and short life span of a packet in the net-work. Therefore, investigating efficient routing for altering TTL and size of buffer is very important for overall network performance. This paper presents a performance analysis based on simulation of the impact of buffer size and TTL for several DTN routing protocols in ICMNs scenario. ONE, i.e., Opportunistic Network Environment is used to simulate the routing protocols considering three performance metrics: delivery ratio, mean latency and overhead ratio. Investigated results mention that Spray-and-Focus (SNF) routing exhibits the best performance for altering TTL and size of buffer than other DTN routing protocols, i.e., Epidemic, PRoPHET, PRoPHETv2, MaxProp, RAPID, and Binary-SNW in the considered performance metrics and simulation scenario.Â